Control of autonomous surface marine vessels for underwater vehicle localization using single range acoustic measurements : doctoral thesis - Mandić, Filip (F. Mandić ; Fakultet elektrotehnike i računarstva, 2019)
Mobile beacon vehicles are used as a navigational aid for autonomous underwater vehicles when performing navigation using single range measurements. They remove the constraints imposed on the underwater vehicle trajectory by executing trajectory that provides informative range measurements. In thesis, a novel control algorithm for the beacon vehicle which ensures observability of the underwater vehicle's navigation filter is presented. The algorithm was tested in real--life environment and the acquired experimental results were validated using a metric proposed in the thesis. In the case when it is not possible to acquire range measurements, time difference of arrival of an acoustic signal can be used for localization. Therefore, control algorithm for an autonomous surface system consisting of two acoustic receivers, capable of measuring the time difference of arrival of an underwater acoustic signal and utilizing this value in order to steer the system towards the acoustic source, is presented. Furthermore, simulation results are shown, where the influence of a constant disturbance caused by sea currents, and a relationship between the time difference of arrival measurement noise and the sensor baseline are investigated. Experimental results in which the algorithm was deployed on two autonomous surface vehicles equipped with acoustic receivers have shown that the algorithm successfully steers the vehicle formation towards the acoustic source, despite the noisy and intermittent measurements.